Impact of Management Development Strategy on Excellence Competition Using Performance as an Intervening Variable of the Private University under the LLDIKTI IX Area - Muhammad Toaha; Hendriadi Hendriadi; Megawaty Megawaty; Al Kausar Al Kausar (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to examine management development strategies for the excellence of private higher education in LLDIKTI IX. The sample in this study was 389 out of 17,589 lecturers working in 328 private universities in the LLDIKTI IX area. The statistical tools used for partial least square analysis with the Structural Equation Method and descriptive statistics. It was found that Development Academic, Curriculum Development, Support Career, and Development Education Have a significant impact on the Performance of Lecturers while Expansion of Education and Developing Competence have no significant impact. Development of Academics, Support Career, and Development of Education Have a significant impact and the Performance of Lecturers' Excellence Competition, while Expansion of Education, Curriculum Development, and Developing Competence have no significant impact on the Excellence competition in private universities in the LLDIKTI IX area.